Case Prevalence Study of Ehrlichiosis among Dogs in Thrissur, Kerala - Sukanya, S; Tresamol, P.V; Vinodkumar, K; Sulficar,S; Siju Joseph (The Indian Veterinary Journal, 2023)
The trend of tick borne infectious diseases are alarmingly increasing and posing a great threat to the health of canine population. Ehrlichiosisis one among the highly prevalent tick borne infectious diseases affecting domestic dogs in Kerala. The present study reports the occurrence of canine ehrlichiosis in Thrissur district and the risk factors associated with its occurrence.Hundred dogs presented to University Veterinary Hospitals, Mannuthy and Kokkalai with clinical signs of fever and lymphadenopathy and thrombopaenia were included in the study. Ehrlichiosis was diagnosed in 55 dogs using peripheral blood as well as buffy coat smear examinationand confirmed further by polymerase chain reaction. Among the dogs positive for Ehrlichia spp., Labrador Retrievers constituted highest numbers followed by Rottweilers and German Shepherds. The case prevalence was more in male dogs compared to females and in the age groupof more than five years followed by two to three year group. The result of present study revealed a higher prevalence of ehrlichiosis among dogs, which warrants the need for adopting suitable control strategies against the disease.